Assessing the role of stakeholders in sustainable groundwater resources management using power-interest matrix (PIM): in Hamedan-Bahar plain, Iran - Sarami-Foroushani, Taraneh; Balali, Hamid; Movahedi, Reza (Frontiers in Water, 2024)
IntroductionMoral Intelligence (MI) as a concept has gained importance Increasing water scarcity as a result of climate change and its coincidence with population growth, economic development, and the resulting rising demand has become an important challenge in most parts of the world. In numerous nations, such as Iran, frequent occurrences of droughts, combined with the extensive utilization of surface and groundwater resources, have resulted in numerous environmental detriments, including a decrease in groundwater levels, land subsidence, deterioration of water quality, and, more recently, the emergence of dust storms due to soil erosion and desertification. In this situation, stakeholders can play an efficient role in water management and the alleviation of water scarcity and its negative environmental externalities in the context of good water governance.MethodThis investigation endeavored to examine the functions and importance of individuals or groups with a vested interest in groundwater resources within the Hamedan-Bahar Plain. Additionally, it aimed to evaluate their influence and motivations through the utilization of the power-interest matrix (PIM) and important-performance matrix techniques. A total of 86 people were identified who could and were allowed to be interviewed through the snowball method. Then a 10-point scale questionnaire was used to rate the questions. To examine the power and interest of the stakeholders, the IPM test was carried out using the smart pls.3 software, and the results were classified based on the average values and the overall impact. The results reveal that 20 institutions and agencies have an effective role in the governance of groundwater resources in the Hamedan-Bahar plain. Furthermore, the analysis of the PIM revealed that the most powerful organizations that play the most important role in the management of the groundwater resources of the studied area are the regional water organization, the representatives of the parliament, and the governor, respectively.Results and discussionBased on the research findings, the governance “power” index of organizations and institutions with power (39.77%) and total impact (0.516) is higher and more effective than the value of benefits with power (36.13%) and total impact (0.48). Accordingly, paying attention to the role and influence of the power of stakeholders will be an important and effective point in the plans and strategies for groundwater resources in the Hamadan-Bahar plain. In the end, strategies are suggested to each stakeholder for better implementation of the programs and strategies.